Introduction: Setting the stage - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
This book is devoted to the complex and controversial relationship between the global trading system and food security. In particular, it aims to answer the question of why trade and the World Trade Organization (WTO) matter for food security. While this relationship has been debated for a long time, the 2001- 2015 period saw some major changes to the global trading sys-tem that changed the terms, and the intensity, of that debate. This period, which coincides with the twenty-year anniversary of the establishment of the WTO, presents a good opportunity to examine the impacts of the integration of agriculture into the global rules- based trading system, initiated with the Uruguay Round in 1995 and implemented gradually until 2004.